Pengaruh Pengembangan Karir Dan Kepuasan KerjaTerhadap Kinerja Karyawan(Studi Kasus Pada Karyawan Pt Inti Sukses Garmindo Tbk Semarang) - , Asriningtyas, Drs. Sri Padmantyo, MBA (2016)
The purpose of this study was to determine the effect of communication and work commitment significantly to the performance of employees at PT Inti Sukses Garmindo Tbk Semarang. The population in this study were all employees of PT Inti Sukses Garmindo Tbk Semarang, totaling 2000 people. Respondents were drawn as many as 100 people, so partially members of the population sampled (study population). Data analysis method used is the classic assumption test, multiple linear regression, goodnes of fit, and t test. The results of this study prove that partially career development (X1), and a job satisfaction (X2) together have a significant impact on employee performance (Y). Later analysis of the coefficient of determination (Adjusted R Square) career development variables (X1) and a job satisfaction (X2) effect by 50,3% to variable employee performance (Y), while the remaining 49,7% is explained by other factors outside the model.